Short-course radiotherapy promotes pro-inflammatory macrophages via extracellular vesicles in human rectal cancer. Issue 2 (18th August 2020) - Stary, Victoria; Wolf, Brigitte; Unterleuthner, Daniela; List, Julia; Talic, Merjem; Längle, Johannes; Beer, Andrea; Strobl, Johanna; Stary, Georg; Dolznig, Helmut; Bergmann, MD, Michael
Abstract : Background: Tumor-associated macrophages (TAM) constitute the most abundant immune cells in the tumor stroma initiating pro-inflammatory (M1) or immunosuppressive (M2) responses depending on their polarization status. Advances in tumor immunotherapy call for a detailed understanding of potential immunogenic mechanisms of irradiation routinely applied in rectal cancer patients. Methods: To test the effects of radiotherapy on TAM, we ex vivo irradiated tissue samples of human rectal cancer and assessed the phenotype by flow cytometry. We furthermore evaluated the distribution of leucocyte subsets in tissue sections of patients after short-course radiotherapy and compared findings to non-pretreated rectal cancer using an immunostaining approach. Organotypic assays (OTA) consisting of macrophages, cancer-associated fibroblast and cancer cell lines were used to dissect the immunological consequences of irradiation in macrophages. Results: We demonstrate that short-course neoadjuvant radiotherapy in rectal cancer patients is associated with a shift in the polarization of TAM towards an M1-like pro-inflammatory phenotype. In addition, ex vivo irradiation caused an increase in the phagocytic activity and enhanced expression of markers associated with stimulatory signals necessary for T-cell activation. In OTA we observed that this alteration in macrophage polarization could be mediated by extracellular vesicles (EV) derived from irradiated tumor cells. We identified high mobility group box 1 in EV from irradiated tumor cells as a potential effector signal in that crosstalk. Conclusions: Our findings highlight macrophages as potential effector cells upon irradiation in rectal cancer by diminishing their immunosuppressive phenotype and activate pro-inflammation. Our data indicate that clinically applied short-term radiotherapy for rectal cancer may be exploited to stimulate immunogenic macrophages and suggest to target the polarization status of macrophages to enhance future immunotherapeutic strategies.